The Model of Entrepreneurial Intention Among College Students with Gender Moderated - Isaskar, Riyanti; Sheliena, Esther; Dewi, Heptari Elita (HABITAT, 2024)
This research was conducted with the aim of analyzing the influence of factors on entrepreneurial intentions of students at the Faculty of Agriculture, Brawijaya University. The number of respondents in this research was 150 respondents who were UB Faculty of Agriculture students. The analysis method used is SEM-PLS analysis with the WarpPLS 7.0 application and uses attitude variables, subjective norms, perceived behavioral control and entrepreneurship education which are moderated by the gender variable. Based on the results of the analysis that has been carried out, it is known that: 1) attitudes, subjective norms, perceived behavioral control, and entrepreneurship education have a positive and significant effect on entrepreneurial intentions among students, 2) gender is significantly able to moderate the independent variables of subjective norms and entrepreneurship education and is reinforcing because the coefficient of the moderating variable is positive, 3) attitudes and perceived behavioral control cannot be moderated by gender. Therefore, self-development programs and skills training are needed as an effort to improve entrepreneurial abilities. Programs that can be organized by the Faculty of Agriculture, Brawijaya University are coaching classes and interactive workshops.